2018
DOI: 10.1016/j.applanim.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal correlates of behavioural profiles and coping strategies in captive capuchin monkeys (Sapajus libidinosus)

Abstract: In this study, we tested the hypothesis that individual differences in behavioural profiles correlate to differences in stress-related behaviours and hormonal levels in captive brown capuchin monkeys (Sapajus libidinosus). Based on a sample of 25 animals, 143 h of behavioural data collection and 518 faecal samples, principal component analyses indicated the existence of four components that characterize the individuals´Genus Normative Behaviour (GNB) (KMO = 0.531, X 2 = 127.672, p < 0.001): 'Feeding', 'Sociabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…The damaging effects of captivity have been well documented. Animals can exhibit stereotyped behavior (Wechsler 1991, Callard et al 2000, Shyne 2006, Jett et al 2017, Poirier and Bateson 2017, Williams et al 2018a, and suffer from increased stress (Bordeleau et al 2018, Ferreira et al 2018, which can eventually result in higher incidence of diseases and mortality (Terio et al 2004, Mitchell et al 2018.…”
Section: Potential Impact Of Commonly Used Methods In Wildlife Researmentioning
confidence: 99%
“…The damaging effects of captivity have been well documented. Animals can exhibit stereotyped behavior (Wechsler 1991, Callard et al 2000, Shyne 2006, Jett et al 2017, Poirier and Bateson 2017, Williams et al 2018a, and suffer from increased stress (Bordeleau et al 2018, Ferreira et al 2018, which can eventually result in higher incidence of diseases and mortality (Terio et al 2004, Mitchell et al 2018.…”
Section: Potential Impact Of Commonly Used Methods In Wildlife Researmentioning
confidence: 99%
“…In studies investigating individual differences in several species, including mammals, birds, and fish (Baugh et al, 2017; Araujo-Silva et al, 2018; Ferreira et al, 2018), a common idea is that the behavioral profile is usually accompanied by physiological responses. Several authors suggest that active vs. passive individuals can be characterized at either end of a continuum, with many intermediate profiles in between.…”
Section: Introductionmentioning
confidence: 99%
“…However, correlations between these variables are not always consistent, even within the same species ( Fernández-Lázaro et al, 2019 ); consequently, animal caretakers may inadvertently over- or under-estimate welfare. Studying personality may aid in understanding why behavioural and physiological measures are not always consistent measures of welfare; for example, recent studies have suggested that individuals may rely on different coping strategies and display alternative stress-indicative behaviours ( Ferreira et al, 2018 ). However, while several studies have highlighted personality as an intrinsic factor predisposing individuals to developing stereotyped behaviours, they typically focus on only one type of behaviour.…”
Section: Applications To Primate Managementmentioning
confidence: 99%
“…Only one study explored how traditional welfare measures may be impacted by personality. Ferreira et al (2018) aimed to quantitively measure the hormonal correlates of personality types and specific stress-indicative behaviours under stress in 25 zoo-housed brown capuchins. The “Active” personality dimension was found to be of particular significance in this study; monkeys assessed as more “Active” displayed more rapid stereotyped behaviours, such as pacing head-twirling, and exhibited higher faecal glucocorticoid metabolite (FGM) levels ( Ferreira et al, 2018 ).…”
Section: Applications To Primate Managementmentioning
confidence: 99%
See 1 more Smart Citation